Uwagi o obowiązkach przedsiębiorcy telekomunikacyjnego w stanach nadzwyczajnych - Gola, Jan; Brzezińska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The occurrence of extraordinary measures may oblige businesses to perform many duties. Importantly, they can address many spheres of financial activity and, in practice, cause some interpretation doubts. The scope of utilization of extraordinary measures results from the nature of juridical institutions. In case of introduction of extraordinary measures avery important role can be played by legal obligations addressing telecommunication companies. Amultitude of orders and prohibitions concerning specific action in practice may raise some doubts. What is important — in the case of the said duties, many fields of legal institutions will apply. In the era of widespread terrorist threat, legal instruments aimed at telecommunications companies can play an important preventive and preservative role. The relevant services, in cooperation with telecommunication operators, may prevent many tragedies and take care of the security of the state in amore effective way.
Keywords: stany nadzwyczajne; przedsiębiorca telekomunikacyjny; obowiązki